Transiently Activated Human Regulatory T Cells Upregulate BCL-XL Expression and Acquire a Functional Advantage in vivo - Issa, Fadi; Milward, Kate; Goto, Ryoichi; Betts, Gareth; Wood, Kathryn J.; Hester, Joanna (Frontiers in Immunology, 2019)
Regulatory T cells (Tregs) can control excessive or undesirable immune responses towards autoantigens, alloantigens and pathogens. In transplantation, host immune responses against the allograft are suppressed through the use of immunosuppressive drugs, however this often results in life-threatening side effects. Tregs can control graft-versus-host disease and transplant rejection in experimental models, providing impetus for the use of Tregs as a cellular therapy in clinical transplantation. One of the major barriers to the widespread use of Treg cellular therapy is the requirement to expand cells ex vivo to large numbers in order to alter the overall balance between regulatory and effector cells. Methods that enhance suppressive capacity thereby reducing the need for expansion are therefore of interest. Here, we have compared the function of freshly-isolated and ex vivo-manipulated human Tregs in a pre-clinical humanized mouse model of skin transplantation. Sorted human CD127loCD25+CD4+ Tregs were assessed in three different conditions: freshly-isolated, following transient in vitro activation with antiCD3/antiCD28 beads or after ex vivo-expansion for two weeks in the presence of antiCD3/antiCD28 beads and recombinant human IL2. While ex vivo-expansion of human Tregs increased their suppressive function moderately, transient in vitro-activation of freshly isolated Tregs resulted in a powerful enhancement of Treg activity sufficient to promote long-term graft survival of all transplants in vivo. In order to investigate the mechanisms responsible for these effects, we measured the expression of Treg-associated markers and susceptibility to apoptosis in activated Tregs. Transiently activated Tregs displayed enhanced survival and proliferation in vitro and in vivo. On a molecular level, Treg activation resulted in an increased expression of anti-apoptotic BCL2L1 (encoding BCL-XL) which may be at least partially responsible for the observed enhancement in function. Our results suggest that in vitro activation of human Tregs arms them with superior proliferative and survival abilities, enabling them to more effectively control alloresponses. Importantly, this transient activation results in a rapid functional enhancement of freshly-isolated Tregs, thereby providing an opportunity to eliminate the need for in vitro expansion in select circumstances. A protocol employing this technique would therefore benefit from a reduced requirement for large cell numbers for effective therapy.